Cervical cancer in pregnancy: a case report - Hariram, Aravinda; Koomson, Matthew (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Cancers during pregnancy are uncommon, with the latest mothers and babies: reducing risk through audits and confidential enquiries across the UK (MBRRACE) report (2023) indicating cancers account for 2% of maternal deaths, highlighting the need for early detection. Cervical cancer, the most common gynecological malignancy in pregnancy, has an incidence of 0.1 to 12.0 per 10,000 pregnancies. The human papillomavirus (HPV) vaccination is expected to significantly reduce cervical cancer rates. We present a case of a 37-year-old multiparous woman with cervical cancer who declined investigations during pregnancy. A white-British woman in her mid-30s presented at 19 weeks gestation with vaginal bleeding. She had low compliance with cervical screening. Despite multiple referrals, she declined urgent colposcopy. At 38 weeks, she had a spontaneous rupture of membranes but did not progress in labor. A cesarean section revealed no tumor in the lower segment. Postnatal examination identified invasive cervical cancer extending to the anterior vagina. Magnetic resonance imaging (MRI) and positron emission tomography-computed tomography (PET-CT) confirmed stage IIIC1r cervical cancer. The patient underwent successful cisplatin-based chemoradiotherapy and was tumor-free at the three-month review. Cervical screening is crucial for early cancer detection and intervention. Reduced participation in screening programs increases the incidence of advanced-stage cervical cancer. Managing patients who decline screening requires a compassionate approach and strategic efforts to encourage compliance. Physiological changes during pregnancy can obscure cancer symptoms, leading to delayed diagnoses and limited treatment options due to fetal risks. Advanced cervical cancer treatment during pregnancy often involves chemotherapy, with radical surgery considered for patients responding well to induction chemotherapy. Evolving follow-up strategies suggest prolonged monitoring due to delayed recurrences when chemotherapy is incorporated.